Communications in the construction projects / Zainal Rahman Abd Kadir - Abd Kadir, Zainal Rahman (2005)
The Malaysian construction industry has always been one of the important sectors of the economy providing the nation with the position to progress in the developing of infrastructure facilities. Drawings, specification, bills of quantities, form of contract, formal procedures, schedules, variation orders and other documents make up the total set of formal project communications and information. It relies on words, numbers and symbols to record information. It is recorded in these documents so that it can be communicated from the head of the author or draftsman to someone else. It is of course, possible to keep records for one's own use but these are rarely of interest in construction project. Construction projects involve a rich variety of forms of communication but they have a single purpose, which is to transfer meaning. This may be to transfer meaning between teams or within teams or between the project and its environment.